2022
DOI: 10.1021/acs.jpcc.2c06013
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the Dynamics and Stability of Self-Assembly: Solvent, Substrate, and Concentration

Abstract: The formation dynamics and stability of CoOEP at the solution/Au(111) interface are captured in situ using scanning tunneling microscopy (STM) in a dynamic solution flow cell at room temperature. The intermediate steps of self-assembly of CoOEP into an ordered monolayer were captured, and fractional coverage as a function of time was measured to extract characteristic parameters of the self-assembly process. Adlayer structure and formation under various solvents are compared to previous studies conducted on HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Small bright features (∼4 Å in size) were observed between pairs of TMPB molecules (denoted as α; green circle in Figure b) as well as at the cell vertices between six molecules (denoted as β; blue circle in Figure b). We attribute these to co-adsorbed solvent molecules, and a simple geometrical consideration suggests that the TCB molecules adopt a vertical configuration, which is stabilized by the interactions with the Au substrate and the TMPB molecules (Figure S5 of the Supporting Information). …”
mentioning
confidence: 99%
“…Small bright features (∼4 Å in size) were observed between pairs of TMPB molecules (denoted as α; green circle in Figure b) as well as at the cell vertices between six molecules (denoted as β; blue circle in Figure b). We attribute these to co-adsorbed solvent molecules, and a simple geometrical consideration suggests that the TCB molecules adopt a vertical configuration, which is stabilized by the interactions with the Au substrate and the TMPB molecules (Figure S5 of the Supporting Information). …”
mentioning
confidence: 99%
“…The STM image of the TCB-CoOEP pseudorectangular (REC) polymorph on Au(111) as obtained by Gurdumov et al is shown in Figure . Also shown in Figure are the DFT optimized lowest energy structures found both for the persistent TCB pseudopolymorph and for the TOL pseudopolymorph.…”
Section: Results and Discusiionmentioning
confidence: 95%
“…The REC and HEX cell dimensions were chosen to match the unit cell dimensions given by Gurdumov et al for the REC and HEX cells. 25 a r = 10a 1 + 11a 2 , b r = −3a 1 + 3a 2 , and a h = a r with b h = 5a 2 , for the REC and HEX cells, respectively, where a 1 and a 2 are the Au(111) atomic lattice vectors and are separated by 120°. Cells had at least 1.8 nm of vacuum space above the highest point on the monolayer surface.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation